2022
DOI: 10.1002/hep4.2080
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone for alcohol use disorder: Hepatic safety in patients with and without liver disease

Abstract: Naltrexone is an approved drug for management of alcohol use disorder (AUD), but data in patients with liver disease (LD) are limited. We aimed to evaluate the safety of naltrexone in those with LD. This is a retrospective cohort of adults with and without LD who were prescribed naltrexone for AUD from 2015 to 2019 in a safety‐net setting. Naltrexone hepatic safety was determined by liver enzyme changes during and after compared to before naltrexone prescription as well as rates of subsequent hospitalization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…[11,12] Previously, naltrexone had not been studied in patients with ALD; however, a recent retrospective review of naltrexone use in patients with AUD with and without ALD demonstrated lower aminotransferase and bilirubin levels during and after naltrexone use in patients with liver disease, including those with cirrhosis. [15] Cumulative survival was similar between those with ALD (with and without cirrhosis) as compared with patients with AUD without ALD. Although patients with cirrhosis (compensated and decompensated) had higher alcohol-associated hospitalizations than those without ALD, none were related to naltrexone use.…”
Section: Acamprosatementioning
confidence: 82%
“…[11,12] Previously, naltrexone had not been studied in patients with ALD; however, a recent retrospective review of naltrexone use in patients with AUD with and without ALD demonstrated lower aminotransferase and bilirubin levels during and after naltrexone use in patients with liver disease, including those with cirrhosis. [15] Cumulative survival was similar between those with ALD (with and without cirrhosis) as compared with patients with AUD without ALD. Although patients with cirrhosis (compensated and decompensated) had higher alcohol-associated hospitalizations than those without ALD, none were related to naltrexone use.…”
Section: Acamprosatementioning
confidence: 82%
“…[76] In individuals with AUD and ALD, neither naltrexone nor acamprosate has been evaluated in randomized controlled trials; however, a recent retrospective study suggested that naltrexone was safe for those with advanced liver disease. [77] Alcoholic hepatitis remains a liver biopsy-confirmed clinical disorder. There is a need for biomarkers that can identify those with ongoing alcohol use, assess inflammation, and predict infectious complications and organ failure.…”
Section: Opportunities For Clinical Trials To Address Societal and Me...mentioning
confidence: 99%
“…In addition, while there are approved pharmacologic therapies for the treatment of AUD, such as acamprosate, naltrexone, and disulfiram, which are based on randomized control trials, there are limited efficacy and safety data on the effectiveness of these therapies in those with ALD, particularly given that disulfiram should not be administered to those with known liver disease due to the risk of DILI 76 . In individuals with AUD and ALD, neither naltrexone nor acamprosate has been evaluated in randomized controlled trials; however, a recent retrospective study suggested that naltrexone was safe for those with advanced liver disease 77 …”
Section: Opportunities For Clinical Trials To Address Societal and Me...mentioning
confidence: 99%
“…11 31 In another retrospective cohort study, naltrexone use in ALD patients including those with cirrhosis was associated with reduced complications and hospitalizations, and there were no naltrexone-related hepatic adverse effects. 32…”
Section: Treatment Of Alcohol Use Disordermentioning
confidence: 99%
“…11,31 In another retrospective cohort study, naltrexone use in ALD patients including those with cirrhosis was associated with reduced complications and hospitalizations, and there were no naltrexone-related hepatic adverse effects. 32 Of the non-FDA-approved medications, baclofen has been studied the most in ALD. The first published RCT on 84 patients reported a twofold increase in cumulative abstinence duration and overall abstinence in patients treated with baclofen.…”
Section: Pharmacotherapies For Treatment Of Alcohol Use Disordermentioning
confidence: 99%